The Effect of Digital-based Literacy on Learning Outcomes of First Grade Students - Azzahra, Rahma Nur; Faipri Selegi, Susanti; Arafat, Yasir (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study aims to determine the effect of digital-based literacy using Wordwall Interactive Media on Learning Outcomes of grade I students of SD Negeri 1 Makarti Jaya. The subjects of this study were grade I students of SDN 1 Makarti Jaya. Data collection techniques in this study using tests and documents with Pre-Experimental design data testing type One-Group pretest-posttest. The results showed that the pre-test results obtained a minimum score of 10 and a maximum score of 70 with an average score of 42.97. while the post-test results obtained a minimum score of 70 and a maximum score of 100 with an average score of 90.27. While the independent sample t-test test in the SPSS version 26 programme obtained a significant value (2-tailed) of 0.000 <0.05, then is rejected and is accepted. So it can be concluded that there is a significant effect of Digital-based Reading and Writing Literacy skills on the Learning Outcomes of grade 1 elementary school students. This study aims to determine the effect of digital-based literacy using Wordwall Interactive Media on Learning Outcomes of grade I students of SD Negeri 1 Makarti Jaya. The subjects of this study were grade I students of SDN 1 Makarti Jaya. Data collection techniques in this study using tests and documents with Pre-Experimental design data testing type One-Group pretest-posttest. The results showed that the pre-test results obtained a minimum score of 10 and a maximum score of 70 with an average score of 42.97. while the post-test results obtained a minimum score of 70 and a maximum score of 100 with an average score of 90.27. While the independent sample t-test test in the SPSS version 26 programme obtained a significant value (2-tailed) of 0.000 <0.05, then is rejected and is accepted. So it can be concluded that there is a significant effect of Digital-based Reading and Writing Literacy skills on the Learning Outcomes of grade 1 elementary school students.